Pelekatan Nama Uray Dalam Hukum Adat Melayu Di Kesultanan Sambas - Wibowo, Ajeng Auliya Ramadhani; Marnita; Prihatin, Angga; Lolita; Aminah, Siti (Fakultas Hukum Universitas Surabaya, 2023)
status, and a person's contribution to society and government. In the Sambas Sultanate, derived names were automatically attached to someone who was a descendant of the Sultanate's family. One of the names known in the Sambas Sultanate and the Malay indigenous community is